Understanding Work Values and Career Preference in Generation Z: is Becoming a Civil Servant Still a Dream Job? - Ma'rifah, Diana; Azizah, Siti Nur; Windasari, Wahyuni (Journal of International Conference Proceedings, 2024)
Generation Z is currently entering the working world. However, there are reports that generation Z is uninterested in working for the government agency, thus government agencies need to understand the principles and values held by this young generation,  so as not to lose potential human resources in the future. Through an analysis of the work values dimensions, this study aims to identify the career preference of generation Z. The respondens in this study were 102 generation Z students at Putra Bangsa University, Indonesia. Data was obtained by distributing questionnaires and then analyzed with descriptive statistics via SPSS. The results show that the majority of generation Z students prefer to work at State-Owned Enterprises or Badan Usaha Milik Negara (BUMN) rather than being civil servants when they graduate from university. The work values believed by the group who want to work in BUMN and the group who want to become civil servants are explained in the results of this study. The results of this study provide an overview of the work values that are the principles of generation Z, so that it can help organizations understand the characteristics of generation Z in the workplace.